2008
DOI: 10.1016/j.rmed.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized colistin as adjunctive treatment of ventilator-associated pneumonia due to multidrug-resistant Gram-negative bacteria: A prospective study

Abstract: Aerosolized colistin may be considered as adjunctive to intravenous treatment in patients with VAP due to MDR Gram-negative bacteria susceptible to colistin in critically ill patients. Although colistin is safe and effective, the best route of administration remains unclear. In addition, controlled comparative studies are needed to establish its effectiveness and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
146
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 23 publications
8
146
1
10
Order By: Relevance
“…There are several studies that have demonstrated clinical use of nebulized colistin suggests good efficiency. 15 Additionally, it was also reported that a single nebulization of colistin was associated with long-lasting highsputum concentrations in patients with CF. 16 It was reported that serum peak concentration of colistin is 18 mg l À1 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have demonstrated clinical use of nebulized colistin suggests good efficiency. 15 Additionally, it was also reported that a single nebulization of colistin was associated with long-lasting highsputum concentrations in patients with CF. 16 It was reported that serum peak concentration of colistin is 18 mg l À1 .…”
Section: Discussionmentioning
confidence: 99%
“…12 These studies were conflicting with earlier studies showing no significant differences with combination therapy; however they were criticized to have small number of patients leading to power limitations. 12,19,26 Efficacy of colistin can be enhanced with the use of another antibiotic, such as rifampicin or carbapenems. [27][28][29] Pintado et al reported that colistin use is effective in MDR Gram negative bacteraemia, with a response rate of 71.7%, when used in combination with aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…However, cost is of great concern, especially when added to the already increased cost needed for the treatment of a critically ill patient. In some studies, with encouraging results for further investigation [58,59], aerosolised antibiotic was given using common and economic ways, via the ventilator circuit or using disposable nebulisers and oxygen flow, thus reducing the cost of treatment.…”
Section: Discussionmentioning
confidence: 99%